2018
DOI: 10.3389/fpsyg.2018.01300
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Cognition: Experts’ Views on Affective-Motivational Research Dispositions in the Social Sciences

Abstract: Research competence (RC) as a key ability of students in the social sciences has thus far been conceptualized as consisting primarily of cognitive dispositions. However, owing to its highly complex and demanding nature, competence in conducting research might require additional affective and motivational dispositions. To address this deficiency in the literature, first, we conducted a qualitative interview study with academic experts (N = 16) in which we asked them to identify challenging research situations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
1
20
0
3
Order By: Relevance
“…These results support previous research, which revealed that RBL projects need to be linked to topics that are of intrinsic interest and need to facilitate active and independent student participation to make research-based learning successful (Gresch et al 2016;Wessels et al 2018). If the preservice teachers could have chosen several aspects of the RBL project, it might have helped them to make sense of the research as the survey did not address whether the preservice teachers were allowed to choose between given instruments such as validated scales or if they were free to create their own instruments such as formulating their own survey questions, it is not known if preservice teachers need freedom in choosing the instrument to enrich their TRP reflection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results support previous research, which revealed that RBL projects need to be linked to topics that are of intrinsic interest and need to facilitate active and independent student participation to make research-based learning successful (Gresch et al 2016;Wessels et al 2018). If the preservice teachers could have chosen several aspects of the RBL project, it might have helped them to make sense of the research as the survey did not address whether the preservice teachers were allowed to choose between given instruments such as validated scales or if they were free to create their own instruments such as formulating their own survey questions, it is not known if preservice teachers need freedom in choosing the instrument to enrich their TRP reflection.…”
Section: Discussionsupporting
confidence: 90%
“…However, ratings were more positive when the preservice teachers investigated their own teaching, problems that they had experienced, or questions in which they had intrinsic interest (Fichten and Weyland 2018;Gresch, Hammann, and Konnemann 2016). Furthermore, an interview study with academic experts revealed that an existing personal thematic interest is needed to begin and master challenging situations in the RBL process (Wessels et al 2018). In accordance with these results about German RBL courses, international studies illustrated that preservice teachers need to be actively and independently participating in an academic research process to appreciate the potentials of research-based learning (Afdal and Spernes 2018;Niemi and Nievgi 2014).…”
Section: Research-based Learning In Teacher Education and Beliefs Abomentioning
confidence: 63%
“…Thus, it can be assumed that successfully conducting research requires a range of different affective-motivational dispositions to cope with the challenges of the research process. A coherent, empirically grounded model of the affective-motivational research dispositions necessary for student research in the social sciences has been recently developed (Wessels et al 2018). It encompasses dispositions that are necessary to begin and to sustain the research process: for example, research interest is needed to initiate a research process, while sustaining it requires frustration tolerance to cope with inevitable setbacks.…”
Section: Affective-motivational Gainsmentioning
confidence: 99%
“…The model of affective-motivational research dispositions (Wessels et al 2018) encompasses nine necessary dispositions for pursuing research in the social sciences, of which four were selected to be investigated in the present study. (1) Value-related interest in research subsumes beliefs about the usefulness of research.…”
Section: Affective-motivational Research Dispositionsmentioning
confidence: 99%
“…Zusätzlich berücksichtigen wir hier die affektiv-motivationale Komponente der Forschungskompetenz, die erst dazu beiträgt, dass vorhandenes Wissen der kognitiven Komponente bei einer potenziellen Forschungstätigkeit zur Anwendung kommt (Weinert, 2001) . Zu dieser affektiv-motivationalen Facette gehören neben einer allgemeinen Unsicherheitsund Komplexitätstoleranz unter anderem das gefühlsbezogene und wertbezogene Forschungsinteresse sowie die forschungsbezogene Selbstwirksamkeit (Wessels et al ., 2018a(Wessels et al ., , 2018b (Ryan & Deci, 2000) . Unterschieden wird zwischen der intrinsischen Motivation, die auf der inhärenten Befriedigung des Handlungsvollzugs beruht, und vier Formen der extrinsischen Motivation, wobei die unterste Stufe die völlig fremdbestimmte Form darstellt und die drei anderen Stufen unterschiedliche Ausprägungsgrade einer zunehmend selbstbestimmten extrinsischen Motivation beschreiben (Krapp & Ryan, 2002, S .…”
Section: Forschendes Lernen Und Forschungskompetenzunclassified